Transformation of Symbolism of a “Mountain/Hill” in John Bunyan’s Pilgrim’s Progress (19th–21st Centuries) - Maria R. Nenarokova (Studia Litterarum)
The article analyzes the functioning of emblems in the text of the Baroque era and their evolution in retellings and adaptations of the Baroque text in the 19th– 21st centuries. John Bunyan’s allegorical treatise Pilgrim’s Progress, rightly called “emblematic theater” in the history of literature, is chosen as the material for the study. One of the frequent elements in the Baroque emblem is the “mountain/hill” image. As part of the emblem, the visual-verbal image “mountain/hill” is a polysemantic word. In each context, this element takes on a new meaning; its connotations can be both positive and negative. In Bunyan’s Pilgrim’s Progress, “mountain/hill” is central to several scenes. Acquiring a negative connotation, this image occurs three times in the meaning of “hell” or “entrance to hell.” In each case, the reader receives additional information that expands his knowledge of the subject. The noun “mountain/hill” acquires positive connotations in emblems with the meaning of repentance and cleansing the personages from sins. The 19th–21st centuries’ adaptations dissolve the allegorical nature of the emblem, destroy or reform its verbal envelope but preserve the emotional coloring of the episodes. The most sustainable emblem is the emblem of “repentance,” which retains its basic elements, albeit in a modified form.